Increasing Customer Engagement on the Potential for Digitalization of MSME Mapping in Mungkung Village, Rejoso District, Nganjuk Regency : Peningkatan Customer Engagement pada Potensi Digitalisasi Pemetaan UMKM di Desa Mungkung, Kecamatan Rejoso, Kabupaten Nganjuk - Figo Afriansyah; Nurjanti Takarini (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
MSMEs in Mungkung Village include various businesses such as culinary, clothing needs, agribusiness, equipment, and automotive industry repairs. Many of them do not understand technological advances, which hinders development. Some MSMEs do not have a logo or brand and only rely on local consumers. This causes ignorance among local residents and potential customers outside the village, due to the lack of even development of mapping. This activity is directed at developing the Mungkung Village community to be technologically literate. Activities focus on increasing customer engagement, digitizing the marketing potential of MSMEs in Mungkung Village through digital maps and increasing their presence and accessibility. Implementation of activities uses qualitative descriptive methods. The results of the activity show that there has been an increase in customer engagement regarding the potential of MSMEs in Mungkung Village through the digital map of MSMEs which can be accessed on the online platform. This program also supports SDGs (sustainable development goals) 8 targets related to decent work and economic growth through strengthening MSMEs.